Industrial applications of nanoparticles. (21st August 2015) - Stark, W. J.; Stoessel, P. R.; Wohlleben, W.; Hafner, A.
<x xml:space="preserve">Abstract</x> This tutorial review analyses where nanoparticle research has left the laboratory and today contributes to valuable products.